Highly efficient (31%) of rubidium-based halide perovskite solar cell using SCAPS-1D simulation - Nure Alam Sakib; Rezvi Ahammed; Md. Tarekuzzaman; Hmoud Al-Dmour; Md. Rasheduzzaman; Md. Nazmus Sakib; M. Moazzam Hossen; Md. Zahid Hasan (AIP Advances)
Perovskite solar cells (PSCs) have emerged as potential substitutes to conventional photovoltaic devices due to their outstanding performance, affordability, and simplicity of construction. This study focuses on optimizing rubidium-based halide perovskite solar cells using numerical simulation tools, specifically SCAPS-1D (Solar Cell Capacitance Simulator), with rubidium germanium bromide (RbGeBr3) as the absorber material. The aim is to improve both efficiency and durability, addressing challenges in creating sustainable and cost-effective photovoltaic technologies. The performance of the proposed solar cell configuration was evaluated by examining various parameters such as the thickness of the absorber, the thickness of the electron transport layer and hole transport layer (HTL), defect densities, temperature, etc. Various hole transport layer materials, including Copper Barium Tin Sulfide (CBTS), Copper Iodide (CuI), PEDOT: PSS, and Spiro-MeOTAD, were analyzed to evaluate their impact on open-circuit voltage, short-circuit current, fill factor, and power conversion efficiency. The findings indicate significant potential for RbGeBr3-based solar cells, with the CBTS HTL yielding the highest efficiency. Among the structures, the ITO/WS2/RbGeBr3/CBTS/Au structure was found to be optimal, achieving a power conversion efficiency of 31.48%, a current density of 26.27 mA/cm2, a voltage of 1.39 V, and a fill factor of 85.76%. This research provides valuable insights for designing and optimizing future perovskite solar cells, contributing to the advancement of renewable and sustainable energy technologies.